Electron transport in the multi-terminal quantum dot system - Taranko, Ewa; Taranko, Ryszard; Wiertel, Małgorzata (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The time-dependent electron transport through a multi-terminal quantum dot system is studied. External microwave fields with arbitrary amplitudes, phases and frequencies are applied to different parts of the system considered. The dependence of the average current and average differential conductance on different parameters of the external microwave fields is analyzed. Special attention is paid to the photon–electron pump effect observed for some values of the quantum dot system parameters.
Optica Applicata, Vol. 35, 2005, nr 3, s. 369-374
Keywords: optyka; photon assisted tunneling; quantum dot